Kriminalisasi Judi Online terhadap Masyarakat dan Sistem Peradilan Pidana - Farantika Dwi Hardini; Azahra Wulandari Aji; Fakhri Azhar; Aditya Amarta Putra; Ali Baroroh Al Muflih (Majelis: Jurnal Hukum Indonesia, 2025)
This article discusses the phenomenon of criminalisation of online gambling in society and its implications for the criminal justice system in Indonesia. Gambling, which is regulated in the Criminal Code (KUHP) Article 303 and Article 303 bis, has undergone transformation in line with the development of information technology. Online gambling, as a form of gambling that utilises the internet, poses new challenges in law enforcement and community protection. In this context, this study aims to analyse the social impact of online gambling as well as the effectiveness of the criminal justice system in handling gambling cases that occur in cyberspace. Through a normative approach and juridical analysis, this article finds that despite clear regulations on gambling, the implementation of the law still faces obstacles, including the lack of public understanding of the risks and legal consequences of online gambling. Therefore, synergy between law enforcement, government, and the community is needed to create more effective awareness and prevention of online gambling practices.